Thermal nondestructive testing and tomography for articles made of carbon-plastic; Defektoskopiya; № 9 - Vavilov V. P. Vladimir Platonovich; De Dzhiovanni A.; Did'epzhan S.; Cengyul'e A. A.; Khul'bert A. S. (1991, 1991)
The results of coordinated USSR-French-USA testing of carbon plastic by dynamic Thermal tomography method were presented. The theoretical and experimental analyses were conducted of one - and double-sided active thermal testing (ATT) of reference carbon plastic sample of 2 mm thickness with the aid of computer thermographic system. The calculation and optimization of main ATT parameters were made using ″Kontrol-2″ program with the application of two-dimensional cylindrical model. The statistical assessment of defect detectability according to Tonimoto criterium was performed. The real and prospective ATT sensitivity taking into account present infrared equipment characteristics was substantiated. The main relations between informative parameters and defect characteristics were discussed.